(untitled) (Research, Society and Development, 2023)
Introduction: Health education in Brazil has changed over the years, due to changes in the dynamics and complexities of health in the country. From this perspective, the reorientation of training in the health area has gained emphasis and has been seeking to bring the pedagogical processes closer to the real health needs of the population, in the assistance provided in the Unified Health System (SUS), with this in mind, the objective of this research was to recognize the repercussions of the Education through Work for Health Program – PET-Saúde/Interprofessionality in the professional training processes. Methodology; This is a qualitative research, with a theoretical framework based on Paulo Freire and data obtained, in 2020, from documentary sources and Culture Circles. Results: It was possible to understand strengths and weaknesses linked to the public notice and the projects contemplated by it, in addition to identifying the power of PET-Saúde in strengthening IPE in training, considering that it improves health care by contributing in the emphasis on dialogue, approximation and resoluteness between the different professional categories, thus seeking to build a more equitable and fair health system with full access. Conclusion: it is perceived that investing in devices such as the PET-Saúde/Interprofessionality Program contributes to the possibility of modifying teaching, contextualizing the training practice and problematizing the necessary advances in the field of health training.